Activation of EphA4 and EphB2 Reverse Signaling Restores the Age-Associated Reduction of Self-Renewal, Migration, and Actin Turnover in Human Tendon Stem/Progenitor Cells - Popov, Cvetan; Kohler, Julia; Docheva, Denitsa (Frontiers in Aging Neuroscience, 2017)
Tendon tissues, due to their composition and function, are prone to suffer age-related degeneration and diseases as well as to poorly respond to current repair strategies. It has been suggested that local stem cells, named tendon stem/progenitor cells (TSPC), play essential roles in tendon maintenance and healing. Recently, we have shown that TSPC exhibit a distinct age-related phenotype involving transcriptomal shift, poor self-renewal and elevated senescence coupled with reduced cell migration and actin dynamics. Here, we report for the first time the significant downregulation of the ephrin receptors EphA4, EphB2 and B4 and ligands EFNB1 in aged-TSPC (A-TSPC). Rescue experiments, by delivery of target-specific clustered proteins, revealed that activation of EphA4- or EphB2-dependent reverse signaling could restore the migratory ability and normalize the actin turnover of A-TSPC. However, only EphA4-Fc stimulation improved A-TSPC cell proliferation to levels comparable to young-TSPC (Y-TSPC). Hence, our novel data suggests that decreased expression of ephrin receptors during tendon aging and degeneration limits the establishment of appropriate cell-cell interactions between TSPC and significantly diminished their proliferation, motility and actin turnover. Taken together, we could propose that this mechanism might be contributing to the inferior and delayed tendon healing common for aged individuals.